2019
DOI: 10.1007/s00592-018-01283-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of suspected MODY patients in Tunisia by targeted next-generation sequencing

Abstract: Aims Maturity Onset Diabetes of the Young (MODY) is a monogenic form of diabetes with autosomal dominant inheritance pattern. The diagnosis of MODY and its subtypes is based on genetic testing. Our aim was investigating MODY by means of next-generation sequencing in the Tunisian population. Methods We performed a targeted sequencing of 27 genes known to cause monogenic diabetes in 11 phenotypically suspected Tunisian patients. We retained genetic variants passing filters of frequency in public databases as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…Similarly, two gene-specific studies conducted in Tunisia identified two variants, one in HNF4A (from 12 patients with diabetes) and the other in the GCK gene (from 23 unrelated patients with diabetes) respectively 17 , 18 . More recently, a third study from Tunisia utilized targeted NGS and identified four variants from 11 patients suspected to have MODY in ABCC8 , HNF1A, and GCK , improving the positive diagnostic rate significantly 19 . There are no studies on MODY published from Kuwait, Bahrain, or Qatar to date.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, two gene-specific studies conducted in Tunisia identified two variants, one in HNF4A (from 12 patients with diabetes) and the other in the GCK gene (from 23 unrelated patients with diabetes) respectively 17 , 18 . More recently, a third study from Tunisia utilized targeted NGS and identified four variants from 11 patients suspected to have MODY in ABCC8 , HNF1A, and GCK , improving the positive diagnostic rate significantly 19 . There are no studies on MODY published from Kuwait, Bahrain, or Qatar to date.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia in F1-III.6 and F1-III.7 probands must be pharmacologically managed according to their genotypes. Furthermore, the c.571C>T mutation has already been reported in another unrelated Tunisian pedigree (20). The main reason for this mutation has never been explained that whether it is due to the gene founder effect or mutational hotspot in Tunisia.…”
Section: Screening Of Gck Gene and Clinical Phenotype Analysismentioning
confidence: 98%
“…Overall, 89 unrelated MODY suspected Tunisian participants (including this study) have been investigated using targeted gene panel sequencing, direct/indirect sequencing, or MLPA testing. Only eleven heterozygous pathogenic variants were found in sixteen unrelated patients (~18%) (16,18,20,21). The results of this study support previous observations of Vaxillaire et al (21) such as (i) the severity of the clinical presentation of non-European cases (including those of Tunisian ancestry) with early-onset diabetes (similar to F2-IV.12 and F4-IV.8 index cases), and (ii) low mutation rates despite the heterogeneous clinical inclusion criteria [although strict in our study (Figure 1)].…”
Section: Clinical Exome Sequencing and Variants Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…ABCC8 gene mutations also constitute common genetic etiology of Permanent and Transient DM [11]. Recently ABCC8 has been recognized as the MODY12 subtype with an increasing number of relative reports [1216].…”
Section: Introductionmentioning
confidence: 99%